Pemidanaan Terhadap Pelaku Tindak Pidana Yang Berusia Lanjut - Purnomo, Bias Cahyo; , Hartanto, S.H., M.Hum (2016)
The purpose of this study is to know differences in sentencing judgment against the decision of punishment against the perpetrators of criminal acts who are elderly with other adults. This research includes normative legal research. Research conducted at the District Court of Ngawi. Source data using secondary data. Data were analyzed using qualitative analysis. The results showed that: First, the completion of the criminal case on the perpetrators of the elderly still refer to the Book of the Law of Criminal Procedure (Criminal Procedure Code), which begins with the inquiry, investigation, prosecution, trial, until the verdict; Secondly, the judges in examining criminal cases trying to find and validate the material based on legal considerations, the facts of the trial, and sociological considerations; Thirdly, there is no difference in the verdict sentencing the offender elderly with other adults. The age factor is not included in mitigating factor penalties. Consideration of the judge in deciding a criminal offense to cut down or harvest forest products without a license against the perpetrators of the elderly still refer to the termination provisions of criminal acts in general is based on legal considerations, the facts of the trial, and sociological considerations.